Perspectives and practices of 'stay-at-home mothers' in relation to the early literacy development of their children - Solomon, Belinda André (University of the Free State, 2009)
The study operates under the belief that the period of early childhood is a critical time in the life of every individual; that it is crucial that a sound foundation is laid as far as a child’s early literacy development is concerned and that the mother’s role in this development is critical. Using the Vygotskian sociocultural perspective of education as a philosophical guide, the study addresses two main questions, namely: What are the perspectives of ‘stay-at-home mothers’ regarding their role in the in the early literacy development of their children; and what are the daily practices of these mothers in this regard? This qualitative, multiple-case study investigates the perspectives and practices of a group of ten middle-to-high-income ‘stay-at-home moms’ and mostly ‘stay-at-home moms’ in relation to the early literacy development of their young children. Over a period of approximately seven months, individual and focus-group interviews and observations were conducted in the homes of participants. The results show that both similarities and differences exist amongst participating mothers in terms of their perspectives and practices. The participants generally operate within the following models (or combinations thereof): facilitator-supporter; companion-teacher; and role model. The participating mothers find their experience as ‘stay-at-home moms’ both rewarding and challenging. They tend to put their challenges, which seem overwhelming to some of them at times, into perspective by considering the current positive results of their investment for their children and for themselves and by looking forward to good results which they expect to see in the future. In spite of the fact that participants are generally knowledgeable about what early literacy entails and about what they should be doing as critical role-players in this development, findings in this study indicate that SAHMs would benefit from both professional and informal support and training. Finally, the perspectives and practices of ‘stay-at-home moms’ is an under-researched area, particularly in South Africa. Educators, parents and the community at large would benefit from increased research in this area as well from the implementation of specific programmes to provide support, training and intervention where necessary.
Keywords: Vygotsky; Mothers’ roles; Sociocultural perspective; Young child; Early literacy development; ‘Stay-at-home mothers’; Early childhood education; Child development; Child development -- South Africa -- Bloemfontein; Dissertation (M.Ed. (Psychology of Education))--University of the Free State, 2009